QUALITY OF LIFE IN WOMEN (CIPEEX, 2024)
QUALITY OF LIFE (QOL) ENCOMPASSES OVERALL WELL-BEING AND IS RELATED TO AN INDIVIDUAL'S PHYSICAL, PSYCHOLOGICAL, AND SOCIAL CONDITION, BEING OF CONSIDERABLE RELEVANCE AND INTEREST IN THE FIELD OF WOMEN'S HEALTH. THE AIM OF THIS STUDY IS TO IDENTIFY THE CHARACTERISTICS ASSOCIATED WITH THE QUALITY OF LIFE OF ADULT WOMEN. THE WHOQOL-BREF QUESTIONNAIRE WAS USED AS A RESEARCH INSTRUMENT, AIMING TO ASSESS QOL IN THE DOMAINS OF PHYSICAL, PSYCHOLOGICAL, SOCIAL RELATIONSHIPS, AND ENVIRONMENT. THIS INSTRUMENT WAS ADMINISTERED THROUGH GOOGLE FORMS, ONLINE, VIA A LINK SENT THROUGH THE WHATSAPP APPLICATION TO 30 WOMEN AGED 18 OR OLDER IN MUNICIPALITIES WITHIN THE STATE OF GOIS, BRAZIL. THE RESULTS OBTAINED SHOWED THAT THE ENVIRONMENT AND PSYCHOLOGICAL DOMAINS OBTAINED HIGHER SCORES IN THE EVALUATION OF QOL, SUGGESTING THAT PARTICIPANTS PERCEIVE A PHYSICAL AND SOCIAL ENVIRONMENT CONDUCIVE TO THEIR WELL-BEING. THIS MAY INCLUDE ASPECTS SUCH AS A SAFE ENVIRONMENT, ACCESS TO ADEQUATE HEALTHCARE SERVICES, LEISURE OPPORTUNITIES, AND HEALTHY ENVIRONMENTAL CONDITIONS. A GOOD PSYCHOLOGICAL STATE IS FUNDAMENTAL FOR QOL AS IT INFLUENCES FUNCTIONING IN ALL AREAS OF LIFE, FROM INTERPERSONAL RELATIONSHIPS TO PROFESSIONAL PERFORMANCE. REGARDING THE RESULTS IN THE PHYSICAL AND SOCIAL RELATIONSHIPS DOMAINS, LOWER SCORES SUGGEST THAT FEMALE PARTICIPANTS IN THE STUDY MAY BE FACING HEALTH PROBLEMS, PERSISTENT PAIN, OR FUNCTIONAL LIMITATIONS THAT NEGATIVELY AFFECT THEIR QOL. ADDITIONALLY, LOWER SCORES IN THE SOCIAL RELATIONSHIPS DOMAIN SUGGEST THAT PARTICIPANTS MAY BE EXPERIENCING DIFFICULTIES IN THEIR SOCIAL INTERACTIONS AND RELATIONSHIPS, WHICH COULD INDICATE SOCIAL ISOLATION, LACK OF EMOTIONAL SUPPORT, OR INTERPERSONAL DIFFICULTIES SUCH AS FAMILY CONFLICTS OR A LACK OF SUPPORT NETWORKS. IN SUMMARY, THESE RESULTS PROVIDE INSIGHTS FOR THE DEVELOPMENT OF INTERVENTIONS AND POLICIES AIMED AT IMPROVING THE QOL OF WOMEN, ADDRESSING AREAS THAT MAY REQUIRE ADDITIONAL ATTENTION TO PROMOTE HOLISTIC WELL-BEING.
Keywords: Quality of Life; Women; Perception; WHOQOL-BREF